Effective Work Function Reduction of Practical Electrodes Using an Organometallic Dimer. (1st March 2016) - Akaike, Kouki; Nardi, Marco V.; Oehzelt, Martin; Frisch, Johannes; Opitz, Andreas; Christodoulou, Christos; Ligorio, Giovanni; Beyer, Paul; Timpel, Melanie; Pis, Igor; Bondino, Federica; Moudgil, Karttikay; et al.
Abstract : The control of the cathode work function (WF) is essential to enable efficient electron injection and extraction at organic semiconductor/cathode interfaces in organic electronic devices. In this paper, ultraviolet photoelectron spectroscopy is used to confirm that depositing an ultrathin layer of the moderately air‐stable pentamethylrhodocene dimer onto various conducting electrodes, by either vacuum deposition or drop casting from solution, substantially reduces their WF to less than 3.6 eV, with 2.7 eV being the lowest attainable value. Detailed measurements of the Rh core levels with X‐ray photoelectron spectroscopy reveal that the electron transfer from the molecule to the respective substrates is responsible for the appreciable WF reduction. Notably, even after air exposure, the WF of the donor‐covered electrodes remains below those of typically used clean cathode metals, such as Al and Ag, rendering the approach appealing for practical applications. The WF reduction, together with the observed air stability of the covered electrodes, demonstrates the ability of the pentamethylrhodocene dimer to reduce the WF for a wide range of electrodes used in all‐organic or organic–inorganic hybrid devices. Abstract : The air‐stable pentamethylrhodocene dimer, applied by either evaporation or drop‐casting, turns essentially any practical conductive material into a low work function electrode. Electron transfer from the dimer to the substrate leads to appreciable reduction of work function. Technological importance is suggested by the stability of the low work function even after prolonged air exposure.